Technique of ACL Reconstruction With Autologous Quadriceps Tendon Bone Graft and Femoral Press Fit Fixation - Wolf Petersen Prof; Julia Ohde Dr. med; Katrin Karpinski Dr. med; Sebastian Bierke Dr. med; Martin Häner Dr. med (SAGE Publishing, 2022)
Background: Recently, there has been an increase in interest in the quadriceps tendon (QT) as an alternative autologous graft option for primary anterior cruciate ligament (ACL) reconstruction. Indication: Anterior cruciate ligament reconstruction in skeletally mature patients (high-risk patients for re-rupture and patients with medial instability). Technique Description: The QT graft is harvested with a 4-cm skin incision over the superior pole of the patella. A double knife and an oscillating saw are used to obtain the QT graft with a bone block from the patella (65 mm x 10 mm graft and 15 mm bone block). Then an arthroscopy is carried out with assessment of the ACL tear and treatment of further intraarticular injuries. ACL reconstruction begins with debridement of the femoral insertion to expose the land marks. The medial portal is used for femoral tunnel drilling with the knee in more than 110° of flexion. A special portal aiming device is introduced via the anteromedial portal and a guide wire is placed in the area of the femoral anteromedial insertion. This guide wire is gradually overdrilled with various drills and dilators of increasing size. The final diameter should be 0.5 mm smaller than the diameter of the bone block of the graft to allow for press-fit fixation. Then, the tibial tunnel is drilled using a tibial drill guide leaving the tibial stump of the original ACL intact. The graft is pulled into the joint through the tibial tunnel until the bone block stops at the femoral tunnel entrance. The bone block is then pushed through the medial portal into the femoral tunnel (press-fit fixation). The tibial fixation is performed with an interference screw and optionally with an extracortical button. Results: Prior studies with 2 years follow-up have shown that the clinical outcomes in primary and revision ACL reconstruction were not significantly different between the use of QT grafts with femoral press-fit fixation and the use of hamstring grafts with femoral suspension fixation. Discussion/Conclusion: Quadriceps tendon bone autograft and femoral press-fit fixation provides an excellent alternative as a graft choice in ACL reconstruction. The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.